Death and burial in Kyivan Rus’ according to written sources - LUTSYK, Iryna (Historia i Świat, 2021)
The spread of Christianity in the lands of Kyivan Rus caused radical, but not rapid, changes in the religious, philosophical, and mental worldviews of contemporary society. Funeral rites were a significant factor in which the feature of the spiritual transformation of local societies was reflected. The proposed study is devoted to the peculiarities of the Christian funeral rite and ceremony in the lands of Kyivan Rus’ and the Galician-Volhynian state, which are covered in written sources of the time. Therefore, the upper chronological date of the study is the XIV century. Their elaboration and systematization led to the construction of the article in a linear way – starting with pre-death, and then post-mortem preparations, directly funeral and memorial service. The analysis and generalization of the funeral rite, characteristic for the Christian Orthodox tradition as a whole, is carried out. At the same time, their separate local elements are highlighted. Some comparisons and parallels between the Rus’ and Byzantine funeral traditions were made.